2018
DOI: 10.2217/fon-2017-0437
|View full text |Cite
|
Sign up to set email alerts
|

MGMT Pyrosequencing-Based Cut-Off Methylation Level and Clinical Outcome in Patients with Glioblastoma Multiforme

Abstract: Our study confirmed that the independent prognostic role of MGMT methylation status. An average level of methylation between all investigated CpGs of 9% may help discriminating between methylated and unmethylated tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…Of note, qMSP is the only method with a comparatively high rate of invalid results (in our cohort: 4/76, 5.3%). Pyrosequencing protocols usually encompass several CpG sites within a differentially methylated region (in our case CpG sites 74‐80, in Felsberg et al 74‐78 22 ), and thus may produce more reliable and quantitative information on the MGMT promoter methylation status, but PSQ tests applied in different centers may interrogate different CpG sites and use distinct evaluation methods 22‐25 . Thus, the cutoff of a mean methylated allele frequency (here: 8%), may differ between different assays.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, qMSP is the only method with a comparatively high rate of invalid results (in our cohort: 4/76, 5.3%). Pyrosequencing protocols usually encompass several CpG sites within a differentially methylated region (in our case CpG sites 74‐80, in Felsberg et al 74‐78 22 ), and thus may produce more reliable and quantitative information on the MGMT promoter methylation status, but PSQ tests applied in different centers may interrogate different CpG sites and use distinct evaluation methods 22‐25 . Thus, the cutoff of a mean methylated allele frequency (here: 8%), may differ between different assays.…”
Section: Discussionmentioning
confidence: 99%
“…The literature surveys identified a lack of consistency in determining methylation cut-off values. A number of authors depend on three categories; unmethylated 0–9%, methylated 10–29% and highly methylated 30–100% ( 49 , 50 ), whereas others rely on two; unmethylated <15% and methylated >15% ( 62 64 ). In addition, several studies use ROC curve analysis to establish the optimal methylation threshold in discriminating diagnostic categories, cancer types, treatment decisions and outcomes, and patient survival ( 62 , 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The methylation index (MI) was calculated as the mean-percent-methylation across all gene CpG sites (three CpG sites of the HS3ST2 gene and six CpG sites of the KLF4 gene). The promoter methylation status was theoretically classified as unmethylated (0–9%), methylated (10–29%) and highly methylated (30–100%) ( 49 , 50 ). Multinomial logistic regression then modelled dependence of the diagnosis on age, BMI, menarche, parity, CpGs and smoking.…”
Section: Methodsmentioning
confidence: 99%
“…Although the current TMZ based CRT has marginally improved survival in MGMT methylated (ie MGMT inactivated) GBM patients, its cytotoxicity is relatively nullified in unmethylated GBM patients [ 17 ]. Recent, recent analysis of quantitative methylation using pyrosequencing on 108 GBM patients revealed that degree of MGMT promoter methylation is directly associated with median progression free survival [ 18 ]. Currently, small molecule inhibitors targeting MGMT are being utilized prior to TMZ based therapy in many clinical trials [ 19 ].…”
Section: Natural Products and Gbmmentioning
confidence: 99%